Research Methods for Business Students - Saunders, Mark, 1959-; Lewis, Philip, 1945-; Thornhill, Adrian (New York : Pearson Prentice Hall, 2009)
Using real-life case studies and written with a student-centred approach, this 5th edition provides students with the necessary knowledge and skills to enable them to undertake a piece of business research making the best use of IT where appropriate.
The nature of business and management research and structure of this book -- Formulating and clarifying the research topic -- Critically reviewing the literature -- Understanding research philosophies and approaches -- Formulating the research design -- Negotiating access and research ethics -- Selecting samples -- Using secondary data -- Collecting primary data through observation -- Collecting primary data using semi-structured, in-depth and group interviews -- Collecting primary data using questionnaires -- Analysing quantitative data -- Analysing qualitative data -- Writing and presenting your project report.
Includes bibliographical references (pages 561-572) and index.
Keywords: Business -- Research; Business -- Research -- Data processing